2004
DOI: 10.1196/annals.1321.028
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroids, Carcinogenesis, and Cancer Progression

Abstract: ABSTRACT:The relationship between sex steroids and cancer has been studied for more than a century. Using an original intact cell analysis, we investigated sex steroid metabolism in a panel of human cancer cell lines, either hormone responsive or unresponsive, originating from human breast, endometrium, and prostate. We found that highly divergent patterns of steroid metabolism exist and that the catalytic preference (predominantly reductive or oxidative) is strictly associated with the steroid receptor status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…Among the genes related to tumor-associated genes, oncogenes and tumor-promoting genes are generally upregulated, whereas the genes related to tumor suppression and the ERα gene are downregulated (Inoue et al, 2002;Teresaka et al, 2004). This is consistent with the effects of estrogen, namely, the promotion of tumorigenesis (Fitzpatrick, 2003;Castagnetta et al, 2004;Yager and Davidson, 2006). For growth-and ionassociated genes and other genes, the expression of various transporters, synthetases, transcription factors, growth response genes, and structural genes was upregulated, indicating an enhancement of cell growth and proliferation (Teresaka et al, 2004).…”
Section: Fl Fl Fl Fl Fla a A A Av V V V Vonoid Estr Onoid Estr Onoid supporting
confidence: 62%
See 1 more Smart Citation
“…Among the genes related to tumor-associated genes, oncogenes and tumor-promoting genes are generally upregulated, whereas the genes related to tumor suppression and the ERα gene are downregulated (Inoue et al, 2002;Teresaka et al, 2004). This is consistent with the effects of estrogen, namely, the promotion of tumorigenesis (Fitzpatrick, 2003;Castagnetta et al, 2004;Yager and Davidson, 2006). For growth-and ionassociated genes and other genes, the expression of various transporters, synthetases, transcription factors, growth response genes, and structural genes was upregulated, indicating an enhancement of cell growth and proliferation (Teresaka et al, 2004).…”
Section: Fl Fl Fl Fl Fla a A A Av V V V Vonoid Estr Onoid Estr Onoid supporting
confidence: 62%
“…In fact, estrogen is a tumorpromoting agent known to increase the risk of breast and uterine cancer in women taking estrogen replacement therapy (Castagnetta et al, 2004;Yager and Davidson, 2006). On the contrary, Asian women (large isoflanoids consumers) and vegetarians have a lower than average breast cancer risk (Limer and Speirs, 2004).…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…Estrogen exposure through hormone replacement therapy (HRT) in postmenopausal women has been associated with cancers of the estrogen-dependent tissues such as breast, cervix, and endometrium (8,9). Studies in animal models have demonstrated that estrogens are established breast carcinogens (10,11). These accumulating data on the causative effects of estrogens led the International Agency for Research (IAR) and the National Toxicology Program of National Institute of Environmental Health Sciences (NIEHS) to declare that steroidal estrogens, as both endogenous and exogenous sources, are "known to be human carcinogens" (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma concentrations of estrogen are generally very low, ranging between 0.4 and 70 nmol/L (38). Tissue concentrations of estrogens are not directly linked to circulating estrogen concentrations as a result of local synthesis, local degradation, and other factors (38)(39)(40). Tissue concentrations of estrogens in the breast are generally much higher than plasma concentrations, with estrone and estrone sulfate concentrations as high as 3 to 5 Amol/L in breast tissue or fluids (38,41,42).…”
Section: Introductionmentioning
confidence: 99%